Amyloid, prions, and other protein aggregates. - Kheterpal, Indu; Wetzel, Ronald (Methods in enzymology ;, 2006)
The ability of polypeptides to form alternatively folded, polymeric structures such as amyloids and related aggregates is being increasingly recognized as a major new frontier in protein research. This new volume of Methods in Enzymology along with Part C (volume 413) on Amyloid, Prions and other Protein Aggregates continue in the tradition of the first volume (309) in containing detailed protocols and methodological insights, provided by leaders in the field, into the latest methods for investigating the structures, mechanisms of formation, and biological activities of this important class of protein assemblies. * Presents detailed protocols * Includes troubleshooting tips * Provides coverage on structural biology, computational methods, and biology.